The Effect of Cord Blood Bile Acid Levels on the Meconium Passage in Utero in Normal Pregnancies - Saynur Sarıcı Yılmaz; Deniz Hızlı; Yaprak Engin Üstün; Engin Yılmaz; Elif Gül Yapar Eyi; Leyla Mollamahmutoğlu (Medical Network, 2016)
OBJECTIVE: To investigate the effect of bile acids on meconium passage in utero in normal pregnancies. STUDY DESIGN: This prospective case control study was performed at Zekai Tahir Burak Women's Health and Teaching Hospital between September 1, 2010 and January 1, 2011. Inclusion criteria were: singleton viable pregnancy, gestational age ≥37 weeks. Exclusion criteria were: presence of any maternal disease, obstetric cholestasis, hepatic infections and multiple pregnancies. Sixty one pregnant women were recruited for the study: 31 women with meconium stained amnion liquid and 30 women with normal amnion liquid. Demographic data and clinical data were collected. Each patient's cord blood gases, cord blood bile acids levels, maternal serum liver function tests and bilirubin levels were investigated. RESULTS: There were no significant differences in maternal age, gestational age, parity and body mass index. We found no differences in the serum bilirubin levels and liver function tests. And there were also no differences in the cord blood gas values between the two groups. The mode of delivery was significantly different between the two groups. We didn't find a statistically significant difference in cord blood bile acid levels between the two groups. CONCLUSION: Cord blood bile acid levels appeared to have no significant effect of meconium passage in normal pregnancies.